EVALUATION THE EFFECT OF PRODUCTION CONDITIONS ON THE QUALITY OF CONCRETE BY USING CONTROL CHARTS (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The objective of this study is to relate the quality of concrete production to thecapability of the production process in such a way that the process capability could indicatethe level of production quality in batching plants. The main idea in this research is that theaccepting and refusing lab tests are not sufficient as quality indices and that the staticallyanalysis including control charts and capability calculations give biter image to theperformance levels of production process in batching plants . In this study, the productionconditions for a batching plant are investigated and the supervision is taken as the effectingfactor on the quality. Large number of testing data of compressive strength are analyzed.Results showed that it is necessary to use more detailed procedure than accepting andrefusing concrete tests.